KEDUDUKAN ‘URF DALAM HUKUM ISLAM - Fariqoini, Azimatul; Aini, Siti Maryam Qurotul (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2023)
In general, 'urf or custom is practiced by all fiqh scholars, especially among the Hanafi and Maliki scholars. Maliki scholars use 'urf or the traditions prevalent among the people of Madinah as a basis for establishing laws and prioritize it over isolated hadiths. Shafi'i scholars often employ 'urf in matters where the legal provisions are not explicitly defined in Sharia or in language usage. The reason scholars accept and utilize 'urf is based on a hadith narrated by Abdullah ibn Mas'ud, as reported by Imam Ahmad in his Musnad, which states: "Whatever the Muslims consider good, it is good in the sight of Allah." Additionally, scholars consider the principle of maslahah (public welfare), meaning that people will face difficulties if 'urf is not considered. Scholars even regard it as a "required condition." When a law is established based on 'urf, its strength is considered equivalent to a law based on explicit textual evidence.